Advanced resin-based composite material with wear-resistant surface and preparation method thereof

By designing a wear-resistant and friction-reducing film on the surface of advanced resin-based composite materials and curing it through an integrated molding process, the serious friction and wear problems of composite materials are solved, and the service life and friction and wear performance of the material are significantly improved.

CN119748982APending Publication Date: 2025-04-04长三角碳纤维及复合材料技术创新中心
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411945913.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing advanced resin-based composite materials have severe friction and wear during use, resulting in a shorter service life of the material and an increased risk of safety accidents.

Method used

An advanced resin-based composite material with a surface wear-resistant surface is adopted, which contains a carrier and filler. The carrier is fabric, non-woven fabric or felt, and the filler is graphite powder, polyether ether ketone powder, etc. Through specific layer structures and functional thin layers design, an wear-resistant friction-reducing film is formed and cured through an integrated molding process.

Benefits of technology

It significantly improves the friction and wear performance of the composite material surface, extends the service life of the material, while maintaining the original mechanical properties of the material, realizing the integration of structure and function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119748982A_ABST
    Figure CN119748982A_ABST
Patent Text Reader

Abstract

The invention discloses an advanced resin-based composite material with a wear-resistant surface and a preparation method thereof, the composite material comprises two layers of carriers and a filler, the filler is located between the two layers of carriers, and the carriers are one of a fabric, a non-woven fabric and a felt. The filler is one or more of graphite powder, polyether-ether-ketone powder, ultra-high molecular weight polyethylene powder, polytetrafluoroethylene powder, carbon fiber powder, polyformaldehyde powder, glass fiber powder, aramid fiber powder and polyamide powder. Different functional materials are introduced to the surface of the composite material to construct a layer-by-layer wear-resistant structure, namely a surface wear-resistant functional layer; in the friction process, all functional materials have a synergistic effect through stress transmission and other forms, surface energy loss is reduced, the surface friction reduction effect is achieved, and therefore the use efficiency of the materials is improved, and the service life of the materials is prolonged. Meanwhile, the original forming process and performance of the composite material are not changed, and integration of high wear resistance and structural performance of the surface of the advanced composite material is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material structure and function integration, and specifically is an advanced resin-based composite material with wear-resistant surface and a preparation method thereof. Background Art

[0002] Advanced resin-based composite materials are made of high-performance fibers as reinforcement and organic polymer resin as matrix. They have excellent mechanical properties, processability, light weight, high strength, corrosion resistance and fatigue resistance. As a structural material, it has been widely used in the aerospace field. Taking the development and application of advanced composite materials for civil aircraft structures as an example, in the 1960s, composite materials began to be developed and applied to structural parts with less stress on civil aircraft, such as leading edges, covers and fairings. And it has been installed and tested in the form of spoilers and rudders on Boeing B737 and B727 models, demonstrating the prospects for the application of such composite materials in composite load-bearing structures. After decades of development, the current use of advanced composite materials in civil aircraft accounts for more than 50% of the total material weight (B787 50%, A350XWB 53%).

[0003] The matrix resins of advanced resin-based composite materials can be divided into two main categories, one is thermosetting resins, including epoxy resins, phenolic resins, bismaleimide, benzoxazine and polyimide, and the other is thermoplastic resins. Considering factors such as material maturity, molding process difficulty and cost, the resin matrix of advanced resin-based composite materials is still mainly high-performance thermosetting resins. Advanced thermosetting composite materials have been widely used in the primary and secondary load-bearing structures of aerospace vehicles, such as wings, fuselages, doors, blades, central wing boxes, etc. With the rapid development of my country's aerospace industry, the demand for aerospace composite materials will continue to grow, and the amount of advanced resin-based composite materials has become an important reference factor for the advancement of aerospace vehicles.

[0004] As the use of composite materials continues to increase, the friction and wear during their use cannot be ignored. According to statistics, nearly 30% of the world's energy is consumed by mechanical friction each year. Mechanical friction can also shorten the service life of parts or structures, leading to failure of mechanical systems and serious safety accidents. However, after curing, thermosetting resins have a high internal cross-linking density. While their composite materials have high strength and modulus, they are also brittle, have low toughness, and have poor wear resistance. Therefore, it is of great significance to improve the wear resistance of such composite materials.

[0005] At present, one of the main ways to improve the wear resistance of thermosetting composite materials is to modify the thermosetting resin matrix to improve the toughness and wear resistance of the matrix resin. The commonly used modification method is to blend specific functional component fillers with the resin matrix, and the fillers include rubber, aluminum oxide, graphene, silicon dioxide, graphene oxide, glass flakes, graphite, soft metals, etc. Although the above method can effectively improve the wear resistance of thermosetting resins, unlike pure resins, advanced composite materials are usually spatial laminated structures established by 2-2 connection degree lamination. This material structure determines the overall performance of the composite material. However, adding wear-resistant functional phase fillers to the original thermosetting resin matrix will inevitably affect the process performance and interface strength of the resin, thereby affecting the molding quality and material properties of the composite material. Another way to improve the wear resistance of composite materials is to apply a friction-reducing and wear-resistant coating on the surface of the cured composite material, and form a wear-resistant layer on the surface of the material after drying. Since the surface of the cured composite material is relatively inert, sandblasting pretreatment is required on the composite surface before applying the friction-reducing and wear-resistant coating, and a transition base layer is required if necessary. The overall process of this technology is cumbersome and time-consuming, which increases the cost of material preparation. The surface coating quality is unstable and the coating strength is low, which cannot further meet the needs of the future development of advanced composite materials. Summary of the invention

[0006] The technical problem to be solved by the present invention is: in view of the technical problems existing in the prior art, the present invention provides an advanced resin-based composite material with wear-resistant surface and a preparation method thereof, which can reduce surface energy loss and achieve surface friction reduction effect, thereby improving the use efficiency and life of the material. In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0007] A wear-resistant advanced resin-based composite material, the composite material comprising a carrier and a filler, the carrier having two layers, the filler being located between the two layers of the carrier, the carrier being one of fabric, non-woven fabric and felt, and the filler being one or more of graphite powder, polyetheretherketone powder, ultra-high molecular weight polyethylene powder, polytetrafluoroethylene powder, carbon fiber powder, polyoxymethylene powder, glass fiber powder, aramid powder and polyamide powder.

[0008] As a further improvement of the above technical solution:

[0009] In the above technical solution, the carrier thickness is 10-150 μm and the surface density is 5 g / m 2 ~110g / m 2 .

[0010] In the above technical solution, the porosity of the filler is 35% to 80%.

[0011] In the above technical solution, the carrier is one or more of polymer fibers, metal fibers, carbon fibers, carbon nanotube fibers, graphene fibers, and glass fibers.

[0012] In the above technical solution, the filler is one of aramid, polyamide, ultra-high molecular weight polyethylene, polyoxymethylene, polyetherimide, polyetherketoneketone, polyphenylene sulfide, polyamideimide and polyimide.

[0013] In the above technical solution, the metal fiber is one of a titanium-based alloy, a tungsten-based alloy and a nickel-based alloy.

[0014] The present invention also provides a method for preparing an advanced resin-based composite material with a wear-resistant surface, comprising the following steps:

[0015] Step S1, cutting and laying composite fabrics or prepregs to obtain a composite preform;

[0016] Step S2, pre-impregnating the carrier and the filler layer with an adhesive film matching the matrix resin of the composite preform to obtain a film;

[0017] Step S3, attaching a friction-reducing film on the surface of the composite preform;

[0018] Step S4: The composite preform and the friction-reducing film are solidified together.

[0019] As a further improvement of the above technical solution:

[0020] In the above technical solution, the prepreg is a continuous fiber reinforced thermosetting resin-based prepreg, and the thermosetting resin matrix includes one of epoxy, phenolic, bismaleimide, unsaturated polyester, benzoxazine, and cyanate ester.

[0021] The surface wear-resistant advanced resin-based composite material and the preparation method thereof provided by the present invention have the following advantages compared with the prior art:

[0022] The present invention discloses an advanced resin-based composite material with wear-resistant surface and a preparation method thereof. A friction-reducing and wear-resistant functional thin layer of a specific structure is introduced into the surface friction area of ​​the composite material. The friction and wear performance of the composite material surface is significantly improved through the synergy, low friction coefficient, self-lubricating and wear resistance of the functional components of the functional thin layer itself. In the advanced resin-based composite material with wear-resistant surface disclosed by the present invention and a preparation method thereof, the selection of the friction-reducing and wear-resistant functional layer includes the carrier material, thickness, surface weight, microstructure morphology and load component of the thin layer. Without changing the original curing and molding process of the composite material, the matrix resin of the composite material and the friction-reducing and wear-resistant functional layer mutually infiltrate, diffuse, phase-change and finally solidify, so that a strong interface is formed between the surface of the composite material and the friction-reducing and wear-resistant functional layer, giving the composite material surface excellent friction-reducing and wear-resistant performance, while retaining its own material performance advantages, and realizing the integration of structure and function. At the same time, the present invention adopts an integrated molding process route, which reduces traditional process steps and improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a structural schematic diagram of the present invention.

[0024] Figure 2 This is a diagram showing the wear condition after the rolling wear test in Example 1 of the present invention.

[0025] Figure 3 This is a diagram of the wear condition after the rolling wear test in Example 1.

[0026] Figure 4 This is a diagram showing the wear condition after the rolling wear test in Example 2 of the present invention.

[0027] Figure 5 This is a diagram showing the wear condition after the rolling wear test in Example 3 of the present invention. DETAILED DESCRIPTION

[0028] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0029] Example 1

[0030] Continuous carbon fiber reinforced epoxy resin unidirectional prepreg, carbon fiber T700-12K, carbon fiber unit area weight 145g / m 2 , resin content 37%, resin curing temperature 180℃, according to [0] 26 The layers are laid in the order of ply to form a composite material preform. Chopped carbon fiber felt is selected with a thickness of 12 μm and a surface density of 10 g / m 2 A film having the same resin as the prepreg is selected and laid on the carbon felt surface of the chopped carbon fiber felt to form a thin film.

[0031] Heat the film to 70℃, select 50 mesh nylon 6 powder and sprinkle it evenly on one side of the film. The loading amount is 40g / m 2 Another layer of carbon felt containing adhesive film is selected to cover the powder-loaded film, and compacted with a roller at a temperature of 70°C to form a layered structure of chopped carbon fiber-nylon 6 powder-chopped carbon fiber, such as Figure 1 As shown, the functional components are initially filled with a resin matrix to form a wear-resistant and friction-reducing film.

[0032] The wear-resistant and friction-reducing film is laid on the surface of the composite material preform, and then compression molding is performed. The process parameters are: compression temperature 180°C, maintained at 5MPa pressure for 120min, and then cooled to 60°C before demoulding to obtain a composite material laminate - Example 1, the volume fraction of carbon fiber V f At the same time, a blank control composite laminate - Comparative Example 1 was prepared under the same process conditions, and the volume fraction of carbon fiber V f It is 62% and the thickness is 3.4mm.

[0033] According to GB / T3960 standard, the sliding friction and wear resistance test of the composite surface was carried out, with 3 samples in each group. The M-200A sliding friction and wear tester was used at room temperature with a load of 20kg, a shaft speed of 200 rpm, and a grinding time of 2 hours under non-lubricated conditions. The wear scar width and mass wear were recorded.

[0034] According to GB / T30314 standard, the rolling wear resistance test of the composite material surface is carried out. Each group of samples consists of 3 samples. H18 grinding wheel is selected. The load is 2kg at room temperature, the shaft speed is 60 rpm, and the number of friction circles is 1200. The rolling wear factor is recorded and published as follows:

[0035]

[0036] Wherein, M1 and M2 are the masses of the specimens before and after the test, respectively, in grams, and N is the number of wear circles.

[0037] The tensile, bending and interlaminar shear properties of the composite materials were tested according to ASTM D3039, ASTM D790 and ASTM D2344. Five specimens were tested in each group and the average value was taken.

[0038] Table 1 shows the test results of the embodiment and comparative example 1. As can be seen from Table 1, compared with the comparative example, the composite material prepared by the present invention has greatly reduced surface volume wear, wear scar width and wear factor while still retaining the in-plane mechanical properties equivalent to those of the comparative example. Figure 2The figure shows the wear of Example 1 after the GB / T30314 test. It can be found that after a long period of rough wear, the protective effect of the wear-resistant layer is obvious, the carbon fiber composite matrix is ​​not exposed, and during the test, the surface wear-resistant functional layer is not found to be delaminated, cracked, pilling, or falling off, achieving structural and functional integration with the composite matrix. In contrast, the wear of Comparative Example 1 is very serious, and the exposed fiber texture is clearly visible after wear, indicating that the wear has broken through the surface of the composite material and penetrated into the carbon fiber layer inside the layer, such as Figure 3 shown.

[0039] Table 1

[0040]

[0041] Example 2

[0042] Continuous carbon fiber reinforced bismaleimide resin unidirectional prepreg, carbon fiber T800-12K, carbon fiber unit area weight 145g / m 2 , resin content 33%, resin curing temperature 210℃, according to [0] 26 The layers are laid in the order of ply to form a composite material preform. Chopped carbon fiber felt is selected with a thickness of 18 μm and a surface density of 15 g / m 2 Select the same adhesive film as the prepreg matrix resin, the weight of the adhesive film is 30g / m 2 , the adhesive film is covered on the upper and lower surfaces of the chopped carbon fiber felt to obtain the adhesive-containing carbon fiber felt.

[0043] The chopped carbon fiber felt was heated to 80°C to make the surface adhesive film and carbon felt initially infiltrated. Polyetheretherketone powder was selected with a particle size of 250 μm and evenly sprinkled on one side of the chopped carbon fiber felt with a loading of 33 g / m 2 Another layer of carbon felt containing adhesive film is covered on the carbon felt loaded with polyetheretherketone powder, and compacted with a roller at a temperature of 80°C to form a layered structure of carbon felt-polyetheretherketone-carbon felt, and the functional components are initially filled with a resin matrix to form a wear-resistant and friction-reducing film.

[0044] The film was laid on the surface of the composite material preform, and then hot-pressed. The process parameters were: curing temperature 210°C, heating rate 2°C / min, maintained at 0.7MPa pressure for 360min, and then cooled to 60°C before being taken out of the can and demoulded to obtain a composite laminate - Example 2, the volume fraction of carbon fiber V f At the same time, a blank control composite laminate - Comparative Example 2 was prepared under the same process conditions, and the volume fraction of carbon fiber V f It is 60.6% and the thickness is 3.5mm.

[0045] Referring to the standards in Example 1, the materials were subjected to sliding friction wear resistance test, rolling wear resistance test and mechanical property test. The results are shown in Table 2. By comparison, it can be found that the sliding friction wear and rolling wear resistance of the sample in Example 2 are greatly improved, and the in-plane mechanical properties are almost unchanged. Figure 4 The figure shows the wear condition of Example 2 after the GB / T30314 test. The protective effect of the wear-resistant layer is obvious, and the carbon fiber composite material matrix is ​​not exposed. At the same time, during the test, no delamination, cracking, pilling, or shedding was found in the surface wear-resistant functional layer, achieving structural and functional integration with the composite material matrix.

[0046] Table 2

[0047]

[0048] Example 3

[0049] Select continuous carbon fiber fabric plain weave, carbon fiber T700-12K, carbon fiber unit area weight 220g / m 2 , select short-cut glass fiber mat, surface density 10g / m 2 . Select room temperature curing low viscosity liquid molding epoxy resin, the resin and curing agent are mixed in a mass ratio of 3:1, and the resin is degassed 3 times after stirring evenly. Select the prepared resin and apply the resin on the glass fiber felt to soak it. Select 50 mesh expanded graphite powder and nylon 66 powder, mix them evenly in a mass ratio of 1:3.5, and then evenly sprinkle them on one side of the film. The attached amount: 40g / m 2 .

[0050] Another layer of glass fiber felt containing adhesive film is covered on the impregnated glass fiber felt, and compacted with a roller at room temperature to form a layered structure of glass fiber-nylon 66 / expanded graphite-glass fiber, and the functional components are initially filled with a resin matrix to form a wear-resistant and friction-reducing film.

[0051] The degassing treated carbon fiber plain fabric is processed according to [0] 16 The film is laid on the surface of the composite material preform in the order of laying layers, and the film is formed by vacuum introduction method. After curing at room temperature for 24 hours, a composite laminate is obtained - Example 3, and the volume fraction of carbon fiber V f At the same time, a blank control composite laminate - Comparative Example 3 was prepared under the same process conditions, and the volume fraction of carbon fiber V f It is 56.5% and the thickness is 3.49mm.

[0052] Referring to the standards in Example 1, the material was subjected to sliding friction wear resistance test, rolling wear resistance test and mechanical property test. The results are shown in Table 3. By comparison, it can be found that the sliding friction wear and rolling wear resistance of the sample in Example 3 are greatly improved, the wear mass is effectively reduced, and the in-plane mechanical properties are almost unchanged. Figure 5 The figure shows the wear condition of Example 3 after the GB / T30314 test. The protective effect of the wear-resistant layer is obvious, the carbon fiber composite material matrix is ​​not exposed, and during the test, no delamination, cracking, pilling, or shedding was found in the surface wear-resistant functional layer, achieving structural and functional integration with the composite material matrix.

[0053] Table 3

[0054]

[0055] The above implementation cases are only preferred embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention has been disclosed as above with preferred embodiments, they are not intended to limit the present invention. Therefore, any simple modification, equivalent changes and modifications made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.

Claims

1. An advanced resin-based composite material with wear-resistant surface, characterized in that: The invention comprises a carrier and a filler, wherein the carrier is provided with two layers, the filler is located between the two layers of the carrier, the carrier is one of fabric, non-woven fabric and felt, and the filler is one or more of graphite powder, polyetheretherketone powder, ultra-high molecular weight polyethylene powder, polytetrafluoroethylene powder, carbon fiber powder, polyoxymethylene powder, glass fiber powder, aramid powder and polyamide powder.

2. The surface wear-resistant advanced resin-based composite material according to claim 1, characterized in that: The carrier has a thickness of 10 to 150 μm and a surface density of 5 g / m 2 ~110g / m 2 .

3. The surface wear-resistant advanced resin-based composite material according to claim 1, characterized in that: The porosity of the filler is 35% to 80%.

4. The surface wear-resistant advanced resin-based composite material according to claim 1, characterized in that: The carrier is one or more of polymer fiber, metal fiber, carbon fiber, carbon nanotube fiber, graphene fiber and glass fiber.

5. The surface wear-resistant advanced resin-based composite material according to claim 1, characterized in that: The filler is one of aramid, polyamide, ultra-high molecular weight polyethylene, polyoxymethylene, polyetherimide, polyetherketoneketone, polyphenylene sulfide, polyamideimide and polyimide.

6. The surface wear-resistant advanced resin-based composite material according to claim 1, characterized in that: The metal fiber is one of a titanium-based alloy, a tungsten-based alloy and a nickel-based alloy.

7. A method for preparing an advanced resin-based composite material with wear-resistant surface, characterized in that: The method for preparing the composite material according to any one of claims 1 to 5 comprises the following steps: Step S1, cutting and laying composite fabrics or prepregs to obtain a composite preform; Step S1, pre-impregnating the carrier and the filler layer with an adhesive film matching the matrix resin of the composite preform to obtain a film; Step S3, attaching a friction-reducing film on the surface of the composite preform; Step S4: The composite preform and the friction-reducing film are solidified together.

8. The method for preparing the surface wear-resistant advanced resin-based composite material according to claim 7, characterized in that: The prepreg is a continuous fiber reinforced thermosetting resin-based prepreg, and the thermosetting resin matrix includes one of epoxy, phenolic, bismaleimide, unsaturated polyester, benzoxazine, and cyanate ester.

Citation Information

Patent Citations

  • Method for enhancing surface abrasion resistance of liquid molding composite material

    CN102924741A

  • Anti-puncture composite fabric structure

    TWM573758U